The Effect of Teaching Games for Understanding (TGfU) on Volleyball Learning Outcomes in Physical Education - Muhammad Rifki Febriyanto; Hermawan Raharjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Volleyball learning in Physical Education at school often faces the problem of low student learning outcomes. The purpose of this study is to evaluate the efficacy of applying the Teaching Games for Understanding (TGfU) learning model in stages—from low to high—with TGfU directly, as well as to ascertain and assess the impact of TGfU on enhancing volleyball learning outcomes. This study employs a pretest–posttest control group design, a quasi-experimental method, and a quantitative methodology. The research sample consisted of two classes selected using a purposive sampling technique, namely experimental class A (32 students) who received TGfU learning with gradual increases and experimental class B (26 students) who received TGfU learning with direct increases. Data were collected through observation and game performance tests using the Games Performance Assessment Instrument (GPAI). With the use of SPSS 25 for Windows, data were examined using normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The findings demonstrated that learning outcomes improved in both classes. Experimental class A saw an average improvement in learning outcomes of 20.75 points, according to the paired sample t-test. In a similar vein, learning results for experimental class B increased on average by 17.62 points. The independent sample t-test revealed a significant difference between the two groups with a significance value of 0.000 (p < 0.05). Therefore, compared to TGfU with direct high-intensity increases, the implementation of the TGfU model with incremental increments, from low to high, is more beneficial in increasing volleyball learning results.